A theoretical study on excited-state dynamical properties and laser cooling of zinc monohydride including spin-orbit couplings - Li, Donghui; Fayyaz, Faiza; Bian, Wensheng (Frontiers in Chemistry, 2024)
By means of highly accurate ab initio and dynamical calculations, we identify a suitable laser cooling candidate that contains a transition metal element, namely zinc monohydride (ZnH). The internally contracted multireference configuration interaction method is employed to compute the five lowest-lying Λ-S states of ZnH with the spin-orbit coupling effects included, and very good agreement is obtained between our calculated and experimental spectroscopic data. Our findings show that the position of crossing point of the A2Π and B2Σ+ states of ZnH is above the v′ = 2 vibrational level of the A2Π state indicating that the crossings with higher electronic states will have no effect on laser cooling. Hence, we construct a feasible laser-cooling scheme for ZnH using five lasers based on the A2Π1/2 → X2Σ+1/2 transition, which features a large vibrational branching ratio R00 (0.8458), a large number of scattered photons (9.8 × 103) and an extremely short radiative lifetime (64 ns). The present work demonstrates the importance of electronic state crossings and spin-orbit couplings in the study of molecular laser cooling.